Of LAP, CUPS, and DRibbles – Unconventional Use of Autophagy Proteins for MHC Restricted Antigen Presentation - Münz, Christian (Frontiers in Immunology, 2015)
Macroautophagy delivers cytoplasmic constituents for lysosomal degradation. Since MHC class II molecules are loaded with lysosomal products for CD4+ T cell stimulation, macroautophagy supports intracellular antigen processing onto MHC class II molecules. The molecular machinery of macroautophagy, however, does not only support this autophagic antigen processing, but seems to also modify extracellular antigen uptake for MHC class II presentation, antigen exocytosis and packaging for improved cross-presentation onto MHC class I molecules. The different membrane trafficking pathways with LAP, CUPS and DRibbles as well as the role that autophagic proteins play in them will be discussed in this review.